Sciatic Nerve Anatomical Variations and Deep Gluteal Syndrome: Clinical Relevance and Current Evidence — A Narrative Literature Review - Leskauskas, Mantas; Nedzinskienė, Laura (Acta medica Lituanica, 2026)
Background: The aim of the study - based on the latest literature, this narrative literature review aims to provide a comprehensive evaluation of deep gluteal syndrome (DGS) and to assess the significance of anatomical variations of the sciatic nerve (SN) in relation to the syndrome.Materials and methods: A review of the scientific literature was conducted using the PubMed, ClinicalKey, and ScienceDirect databases. Publications were selected from 2015 to 2026. All publications were written in English. The following keywords and their combinations were used during the search: “deep gluteal syndrome,” “sciatic nerve variations,” “sciatic nerve entrapment,” and “piriformis syndrome.”Results: The sciatic nerve, characterized by significant anatomical variability in the deep gluteal space, may result in altered biomechanics and predispose the nerve to compression. Anatomical variations of the sciatic nerve, depending on their relationship with the piriformis muscle, are categorized according to the Beaton and Anson classification (types A–F). In recent decades, the term “deep gluteal syndrome” has come into use, encompassing extrapelvic non-discogenic sciatic nerve compressions. The syndrome most commonly manifests as persistent, “shooting” pain that worsens after prolonged sitting and radiates toward the back of the knee, hip, and/or gluteal region, as well as dysesthesia and nocturnal pain. There is currently no gold standard for the diagnosis of DGS. Diagnostic criteria may include compression of the SN in the deep gluteal region, sciatica-like pain, and a non-discogenic origin of symptoms. First-line treatment options include physical therapy, nonsteroidal anti-inflammatory drugs (NSAIDs), muscle relaxants, and rest. In addition, intramuscular injections of a local anaesthetic may be administered to alleviate symptoms. If conservative treatment proves ineffective, surgical nerve decompression should be considered.Conclusions: The most common abnormal sciatic nerve variation worldwide is the type B variant. Although anatomical variations of the sciatic nerve alter its biomechanics, they have no direct, statistically significant association with the development of deep gluteal syndrome, according to the latest literature. Anatomical variations of the sciatic nerve may be considered a predisposing factor that increases the risk of DGS when additional primary etiological factors are present. However, more comprehensive scientific studies are needed to assess this.
Keywords: sciatic nerve; deep gluteal syndrome; anatomical variations